A Systematic Literature Review on Knowledge Retention for Mitigating Knowledge Loss in Startups: Trend, Technologies, and Framework - Farzana Hadifa; Mahdi Ali Ghazi Yuana Putra; Dana Indra Sanuse; Sofian Lusa; Icha Mailinda (Green Publisher Indonesia, 2026)
Employee turnover is a critical challenge in startups, as valuable knowledge is often lost when employees leave the organization. This loss occurs due to the lack of effective knowledge retention practices, particularly in converting tacit knowledge into explicit knowledge. This study investigated knowledge retention in startup environments through a Systematic Literature Review (SLR) following PRISMA 2020 guidelines, including study identification, selection, data extraction, and synthesis. 21 relevant studies published between 2020 and 2025 were analyzed with Atlas.ti to identify key technologies and domains shaping knowledge retention frameworks. Four major technology groups are identified: Data Analytics & Intelligence Technologies, Cloud-Based Knowledge Management Systems, Knowledge Sharing and Collaboration Platforms, and Knowledge Repositories, in addition, 14 subdomains within the people, process, and technology domains were synthesized into a conceptual framework, highlighting knowledge retention as a socio-technical process. This research contributes by addressing the lack of research on knowledge retention in startup contexts and offers a conceptual foundation to support startups in developing knowledge retention strategies.